The Role of Technology in Enhancing Multicultural Education and Promoting Cultural Awareness Among Students in Fiji - Prasad, Bijita; Raiula, Taraivini; Alasa, Victor Mafone (Jurnal Pendidikan Abad Ke-21, 2024)
Fiji, a multicultural nation, presents an opportunity to leverage technology for enriching educational experiences. This research explores the potential of technology to enhance multicultural education and promote cultural awareness among students in Fiji. The study investigates how technology can be used to facilitate access to diverse cultural information and resources, promote intercultural communication and collaboration, and create immersive and interactive learning experiences. The research employs a qualitative approach, combining a literature review with a survey of educators and students in Fiji. The findings aim to inform the development of effective strategies for integrating technology into multicultural education, ultimately fostering a more inclusive and culturally aware learning environment for Fijian students.